Optical Properties of Surface Layers Enhanced Raman Scattering - Mattei, G.; S. N., Aqida (Elsevier, 2016)
This article elaborates on surface-enhanced Raman scattering (SERS) technique, increase of Raman scattering due to various factors namely; chemical effect, charge transfer, resonance, and electromagnetic field amplification. The electromagnetic enhancement mechanism is caused by electric field from the surface, surface plasmons excitation and surface electromagnetic waves, and metal particles. SERS technique increased the Raman intensity by factors up to 1015 using graphene-based with noble metallic nanostructure substrate such as silver and gold nanoparticles.